Information in the games of pursuit - Jačiauskas, I. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. П. Ячяускас. Вопрос информации в некоторых играх преследования I. Jačiauskas. Informacija kai kuriuose persekiojimo lošimuose